MORPHOTAXONOMY AND ALLOMETRY OF OESTRUS OVIS (LINNÉ, 1758)LARVAE (DIPTERA: OESTRIDAE: OESTRINAE) - 1.1.1 M. Kamal1; G. Yasmeen; F. Naz; N. U. Saher; N. Ahmad; W. Khan; G. J. Yousafzai (Journal of Animal and Plant Sciences, 2020)
The larvae of Oestrus ovis Linné, 1758 are well-known parasites of goats and sheep. Larval instars of O. ovis are described based on specimens collected from nasal cavities, frontal sinuses and base of the horns of goats from Karachi, Pakistan. Three instars of larvae are described in detail, including body coloration, dorsal and ventral body spines and D- shaped spiracles. Colored illustrations of various larval instars along with typical characters have been given. We also give a key to the third instar larva with some modifications. The mean length (15.65±4.29), width (6.043 ±1.70) and weight (356.3±168.4) of O. ovis larvae were calculated. The one way ANOVA showed significant differences (P<0.05) in length, width and weight of three larval instars of O. ovis. Larvae growth relationship showed negative allometry between weight-length and weight-width, while length-width showed isometry.
Keywords: Oestrus ovis; Morphometric measurements; Taxonomy; Morphology; Karachi; Pakistan